Kajian Meningkatkan Keupayaan Rangkaian Komputer di Kampus UiTM Cawangan Kedah - Mohamad Yusof, Darus (2003)
This study aimed at upgrading the UiTM Kedah branch computer networking capabilities with the focus on data transmission. The case study made use of the Netwin methodology. Each activity in this study was based on the phases in this particular methodology. Analyses were done on the information network currently received. This information was obtained from the discussion with the IT personnel and also from the testing done. From the analyses, suggestions were given to upgrade the computer networking performance. These suggestions did not take into consideration the cost that might involve. Apart from that, this study was not meant to reach the implementation stage because it would involve the cost and approval from the UiTM itself The computer networking in UiTM Kedah branch was connected to other UiTM branches computer networking through the use of COINS technology introduced by Syarikat Telekom Malaysia Berhad. It was hope that this study could be beneficial to the UiTM Kedah branch in upgrading the computer networking performance especially in the iaspect of data transmission.